Your body is your own : a book for parents and children to read together - Bahr, Amy C.; Green, Frederick Bennett (New York : Grosset & Dunlap, 1986)
Simple text and illustrations discuss how to tell the difference between acceptable physical affection and unacceptable touching and how to handle such situations.
"Ages 4-7"--P. 4 of cover.
School Library Journal
3.0
K-3
Keywords: Child molesting -- Juvenile literature; Child molesting -- Prevention -- Juvenile literature; Child molesting; Safety; Child abuse; Safety education